Schoengastia propria Audy and Womersley 1957 - Stekolnikov, Alexandr A. (Zenodo, 2021)
Schoengastia propria Audy and Womersley, 1957 Schoengastia propria Audy and Womersley, 1957: 367, fig. 8; Nadchatram et al. 1980: 269, 280; Fernandes & Kulkarni 2003: 324, fig. 106; Chaisiri et al. 2016: 332. Schoengastia (Schoengastia) propria : Vercammen-Grandjean 1965b: 82. Type deposition. ZSI. Type data. Ex Fowlea piscator (syn. Natrix piscator ), India, Bombay (currently Mumbai). Hosts. RODENTIA: Bandicota indica, Rattus rattus SQUAMATA: Fowlea piscator . Distribution. India, Thailand. : Published as part of Stekolnikov, Alexandr A., 2021, A checklist of chigger mites (Acariformes: Trombiculidae) of Southeast Asia, pp. 1-163 in Zootaxa 4913 (1) on page 94, DOI: 10.11646/zootaxa.4913.1.1, http://zenodo.org/record/4448915 : {"references": ["Womersley, H. & Audy, J. R. (1957) Malaysian Parasites-XXVII. The Trombiculidae (Acarina) of the Asiatic-Pacific Region: A revised and annotated list of the species in Womersley, 1952, with descriptions of larvae and nymphs. Studies from the Institute for Medical Research, Federation of Malaya, 28, 231 - 296.", "Fernandes S. J., S. & Kulkarni, S. M. (2003) Studies on the trombiculid mite fauna of India. Records of the Zoological Survey of India, Occasional Paper, 212, 1 - 539.", "Chaisiri, K., Stekolnikov, A. A., Makepeace, B. L. & Morand, S. (2016) A revised checklist of chigger mites (Acari: Trombiculidae) from Thailand, with the description of three new species. Journal of Medical Entomology, 53, 321 - 342. https: // doi. org / 10.1093 / jme / tjv 244", "Vercammen-Grandjean, P. H. (1965 b) Trombiculinae of the world. Synopsis with generic, subgeneric, and group diagnoses (Acarina, Trombiculidae). George Williams Hooper Foundation, University of California, San Francisco, California, 191 pp."]}